MAIN PROBLEMS AND DIRECTIONS OF MODERN RESEARCH IN THE FIELD OF PROFESSIONAL ACTIVITY (ON THE EXAMPLE OF LABOR PROTECTION): Array - Dreval, Yu.; Sharovatova, O.; Zhyhlo, A.; Bryhada, O. (Municipal economy of cities. Series: «Economy science», 2022)
It is noted that today the number of new challenges and dangers that threaten the proper safety and health of workers is growing rapidly. Of particular note is the need to counter the COVID-19 pandemic, which is having a devastating effect on the safety and health of citizens and on modern public relations in general, a unprecedented threat on a global scale. At the same time, with the development of the information society and the emergence of new technologies, new resources are emerging to improve the share of social and labor relations. This applies both to purely applied aspects of the acquisition and application of acquired knowledge, and to determine the prospects for the protection of working people, taking into account the most important issues of today. All this requires the urgent development and improvement of modern research in the field of professional activity. A necessary precondition for research in the field of professional activity was a careful analysis of the latest factors and threats that greatly complicate the search for optimal forms and methods of safety in the workplace (first of all, the need to combat the COVID-19 pandemic, exclusively by retroactive measures and means). Today, the fact that they should be conducted on an integrated basis and with the obligatory involvement of a systematic approach is becoming increasingly important. The applied aspect of the organization of research in the field of professional activity should be taken into account, which is that the quality of such research depends on the use of resources and opportunities that arise due to the development of the information society and the emergence of new technologies. The need to develop a full-fledged information support, through which the researcher not only receives the appropriate information necessary for his own research work, but also has additional opportunities for a full creative search; the actual formation of information support is the first stage of any study.